FEASIBILITY OF 5G NETWORK IN EDUCATIONAL INSTITUTIONS: A CASE STUDY AT SMKN 1 CILEGON USING COST BENEFIT ANALYSIS (CBA) - Panjaitan, May Hendra (UTSAHA: Journal of Entrepreneurship, 2025)
Telecommunication technology has advanced to the fifth-generation (5G) era, offering unprecedented opportunities for digital transformation in educational sectors. In Indonesia, 5G penetration has reached approximately 2.9%, indicating uneven distribution patterns, particularly affecting vocational education institutions such as SMKN 1 Cilegon, which requires robust digital infrastructure to enhance learning quality and competitiveness. This study aimed to assess the economic feasibility of implementing a 5G network at SMKN 1 Cilegon using the Cost Benefit Analysis (CBA) methodology. The proposed implementation was designed utilizing one microcell Base Transceiver Station (BTS) unit to satisfy coverage requirements for a 2.1-hectare area serving 1,000 daily active users. Financial projections incorporated Capital Expenditure (CAPEX) of USD 25,400, annual Operational Expenditure (OPEX) of USD 7,400, monthly user revenue of USD 20, and comprehensive cash flow analysis over a five-year period to determine Net Present Value (NPV) using a 10% discount rate. The results demonstrated a positive cumulative NPV of USD 726,304.6 by the fourth year, confirming that 5G deployment at SMKN 1 Cilegon is economically viable. The findings indicate that minimal infrastructure requirements combined with favorable cost structures support 5G implementation to accelerate digital transformation, strengthen student competencies, and foster enhanced collaboration between educational institutions, vocational training providers, and industry stakeholders within Industry 4.0 frameworks.